2017
DOI: 10.1016/j.jid.2016.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Fibroblasts Promote Alternative Macrophage Activation Improving Impaired Wound Healing

Abstract: Tight control of inflammation is required for tissue repair and wound healing and depends on alternative polarization of macrophages as checkpoint for inflammatory resolution. Its perturbations lead to impaired regeneration. Administration of cells/cell factors capable of reversing inflammation and rescuing alternative polarization could be promising for treating inflammatory diseases. We show that human dermal fibroblasts (dFb) are ideal candidates for such a task by demonstrating a new function of these cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 66 publications
(89 reference statements)
3
25
0
Order By: Relevance
“…Although we found no significant difference in the absolute number of macrophages in TSG-6 null versus WT wounds, we did determine that macrophages in TSG-6 null wounds were skewed towards an M1 phenotype. This is in agreement with previous studies showing that and immobilized HC-HA complexes can drive macrophages to a more anti-inflammatory phenotype (Ferrer et al 2017;He et al 2013;Mittal et al 2016), and that TSG-6-producing MSCs can lower proinflammatory marker expression and increase anti-inflammatory M2 macrophages in a colitis model (Song et al 2017). From several lines of evidence, including the fact that M2 macrophages are known to promote tissue repair, and that M1 macrophages are greatly increased in chronic wounds such as diabetic ulcers, it is becoming clear that controlled regulation of macrophage phenotype is critical for proper wound healing (Hesketh et al 2017;Khanna et al 2010;Krzyszczyk et al 2018).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although we found no significant difference in the absolute number of macrophages in TSG-6 null versus WT wounds, we did determine that macrophages in TSG-6 null wounds were skewed towards an M1 phenotype. This is in agreement with previous studies showing that and immobilized HC-HA complexes can drive macrophages to a more anti-inflammatory phenotype (Ferrer et al 2017;He et al 2013;Mittal et al 2016), and that TSG-6-producing MSCs can lower proinflammatory marker expression and increase anti-inflammatory M2 macrophages in a colitis model (Song et al 2017). From several lines of evidence, including the fact that M2 macrophages are known to promote tissue repair, and that M1 macrophages are greatly increased in chronic wounds such as diabetic ulcers, it is becoming clear that controlled regulation of macrophage phenotype is critical for proper wound healing (Hesketh et al 2017;Khanna et al 2010;Krzyszczyk et al 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, TSG-6 protein is able to inhibit neutrophil migration via the TSG-6 Link domain (Cao et al 2004;Getting et al 2002) which interacts with neutrophil chemokines such as human CXCL8, and with glycosaminoglycans (GAGs) on endothelial cell surfaces (Dyer et al 2016;Dyer et al 2014). Furthermore, TSG-6, as well as HC-HA complexes, have been shown to promote the polarization of macrophages to an alternatively activated/ anti-inflammatory M2 phenotype instead of the classically activated/ proinflammatory M1 phenotype (Ferrer et al 2017;He et al 2013;Mittal et al 2016). Given the ability of TSG-6 to regulate the behavior of neutrophils and macrophages, we postulated that TSG-6 may be important in cutaneous wound healing.…”
Section: Introductionmentioning
confidence: 98%
“…As opposed to moDCs, fibroblasts secretions appeared to prevent early steps of monocytes differentiation and pro‐inflammatory profile in our study. Although fibroblasts are typically described as contributing to monocytes chemotaxis, recent macrophages studies have reported anti‐inflammatory activities for fibroblasts on monocytes/macrophages . Collectively, these data and our study highlight an interesting role for fibroblasts in fine tuning the pro‐ and anti‐inflammatory balance.…”
Section: Discussionsupporting
confidence: 72%
“…Below we describe several emerging novel therapeutic approaches, which promote prowound healing activity of macrophages. These methods rely either on the stimulation of the prohealing M2 phenotype of the wound macrophages using environmental changes; antiapoptotic factors;, growth factors or supporting cells (fibroblasts or mesenchymal stem cells); or on the depletion, silencing, or switching the phenotype of the pro‐inflammatory M1 macrophages present in the wound (Ferrer et al, ; Goren et al, ; Guo et al, ; Ishida et al, ; Krzyszczyk, Schloss, Palmer, & Berthiaume, ).…”
Section: The Limitations Of Wound Healing Research and Therapies Potmentioning
confidence: 99%